2018
DOI: 10.4028/www.scientific.net/msf.936.93
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Effect on T’-Pr<sub>2-</sub><i><sub>x</sub></i>Ce<i><sub>x</sub></i>CuO<sub>4</sub> Nanopowders in the Underdoped Regime Studied by X-Ray Absorption near Edge Structure

Abstract: This research is aimed to examine oxidation state of Copper (Cu) in both as-synthesized and reduced T’-Pr2-xCexCuO4 (T’-PCCO) with x = 0, 0.10, and 0.15 using Cu K-edge x-ray absorption near edge structure (XANES). The T‘-PCCO nanopowders were successfully synthesized by the chemically dissolved method with HNO3 as a dissolving agent continued by calcination at 1000°C for 15 h. The reduced T’-PCCO nanopowders were obtained by reduction annealing process at 700°C for 5 h under Ar gas atmosphere. The analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Moreover, in the as-synthesized samples, the absorption near-edge spectra studied by Asano et al [6] shows a linear Ce-dependence of electron number at the Cu site. This is in line with the recent study by Irfanita et al [7] in which the addition of Ce doping can decrease the oxidation state of the Cu ions. The increasing number of electrons corresponds to the decreasing oxidation state affecting crystalline defects at around CuO2-plane.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, in the as-synthesized samples, the absorption near-edge spectra studied by Asano et al [6] shows a linear Ce-dependence of electron number at the Cu site. This is in line with the recent study by Irfanita et al [7] in which the addition of Ce doping can decrease the oxidation state of the Cu ions. The increasing number of electrons corresponds to the decreasing oxidation state affecting crystalline defects at around CuO2-plane.…”
Section: Introductionsupporting
confidence: 93%
“…Furthermore, Ce-doping may play an important role in affecting the weak ferromagnetism. R. Irfanita et al [7] have reported that the addition of Cedoping into T'-PCCO can reduce the Cu oxidation state. This is an evidence of electron donor to fill in the Cu 3d band, and therefore, causing a lower amount of vacancy around the CuO2-plane and decrease the magnetic moment of ferromagnetism on the surface of the nanoparticles.…”
Section: Samplementioning
confidence: 99%